The complete plastid genome of Vanda xichangensis (Orchidaceae, Aeridinae) - Liu, Ding-Kun (Mitochondrial DNA B Resour, 2019)
The complete plastid genome of Vanda xichangensis was determined and analyzed in this work. The plastome was 146,681 bp in length with 83,920 bp of the large single-copy (LSC) region, 11,751 bp of the small single-copy (SSC) region and 25,505 bp of the inverted repeat (IR) regions. The genome contained 120 genes, 74 protein-coding genes, 38 tRNA genes, and 8 rRNA genes. Phylogenetic analysis suggested V. xichangensis is sister to V. richardsiana plus V. falcata.